Linking Self-Control to Voluntary Behaviors at Workplace: The Mediating Role of Job Satisfaction - Wang, Yu-Jie; Chen, Kui-Yun; Dou, Kai; Liu, Yao-Zhong (Frontiers in Psychology, 2021)
Voluntary work behavior (VWB) refers to spontaneous workplace behaviors that extend beyond role norms, including extra-role behaviors that benefit the organization (i. e., organizational citizenship behavior, OCB) and negative behaviors that may harm the organization (i.e., counterproductive work behavior, CWB). This study examined the relationship between self-control and VWB and the mediating role of job satisfaction. A total of 1,101 full-time employees from China completed a battery of self-report measures online. The results show that self-control positively predicts employees' OCB and negatively predicts employees' CWB. Moreover, job satisfaction significantly mediates the relationship between self-control and OCB/CWB. The results confirm that employees with high self-control are more public-spirited, which previous studies have described as being “highly committed” (high OCB) or “less harmful” (low CWB). This finding closely relates to the observation that employees with high self-control tend to have more satisfying work outcomes or higher workplace status than those with low self-control.